Evaluation of cloud‐resolving and limited area model intercomparison simulations using TWP‐ICE observations: 1. Deep convective updraft properties. Issue 24 (18th December 2014) - Varble, Adam; Zipser, Edward J.; Fridlind, Ann M.; Zhu, Ping; Ackerman, Andrew S.; Chaboureau, Jean‐Pierre; Collis, Scott; Fan, Jiwen; Hill, Adrian; Shipway, Ben
Abstract Ten 3‐D cloud‐resolving model simulations and four 3‐D limited area model simulations of an intense mesoscale convective system observed on 23–24 January 2006 during the Tropical Warm Pool‐International Cloud Experiment (TWP‐ICE) are compared with each other and with observed radar reflectivity fields and dual‐Doppler retrievals of vertical wind speeds in an attempt to explain published results showing a high bias in simulated convective radar reflectivity aloft. This high‐bias results from ice water content being large, which is a product of large, strong convective updrafts, although hydrometeor size distribution assumptions modulate the size of this bias. Making snow mass more realistically proportional to D2 rather than D3 eliminates unrealistically large snow reflectivities over 40 dBZ in some simulations. Graupel, unlike snow, produces high biased reflectivity in all simulations, which is partly a result of parameterized microphysics but also partly a result of overly intense simulated updrafts. Peak vertical velocities in deep convective updrafts are greater than dual‐Doppler‐retrieved values, especially in the upper troposphere. Freezing of liquid condensate, often rain, lofted above the freezing level in simulated updraft cores greatly contributes to these excessive upper tropospheric vertical velocities. The strongest simulated updraft cores are nearly undiluted, with some of the strongest showing supercell characteristics during the multicellular (presquall) stage of the event. Decreasing horizontal grid spacing from 900 to 100 m slightly weakens deep updraft vertical velocity and moderately decreases the amount of condensate aloft but not enough to match observational retrievals. Therefore, overly intense simulated updrafts may additionally be a product of unrealistic interactions between convective dynamics, parameterized microphysics, and large‐scale model forcing that promote different convective strengths than observed.